(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
Development of new Clotrimazole derivatives was studied here. Automated prediction of protein-small molecule interactions is one of the most challenging problems in structural biology as well as in medicinal chemistry. Many biological studies, both in academia and in industry, may benefit from credible high-accuracy interaction predictions. The molecular interactions with target protein have been discussed. A target based designing of new derivatives for future drug development presented, which can be further informative and marketed if their biological significance stand out better than the marketed one. The report concludes with a description of the initial efforts to prepare synthesized compounds to recognize as better antifungal agents than the regular prescribed drugs in market. The in silico drug designing leading to initial successes are described along with future directions.